2009
DOI: 10.1089/end.2009.0339
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Percutaneous Nephrolithotomy in Patients with Chronic Kidney Disease

Abstract: PCNL has a favorable impact in CKD patients with good clearance rates and good renal functional outcome. PCNL in this high-risk CKD population is to be done with care and full understanding of its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
3
26
2
1
Order By: Relevance
“…Most patients had stage 3 or 4 CKD and most showed improvement or stabilization in renal function after PCNL. Postoperative complications and peak eGFR were the main factors predicting deterioration of kidney function during follow-up [35] . In another study, Bilen et al [36] evaluated 185 subjects with eGFR < 60 mL/min per 1.73 m² undergoing PCNL and found the average preoperative eGFR substantially improved from 42.4 to 48.4 at three months followup.…”
Section: Retrograde Intrarenal Surgerymentioning
confidence: 97%
See 2 more Smart Citations
“…Most patients had stage 3 or 4 CKD and most showed improvement or stabilization in renal function after PCNL. Postoperative complications and peak eGFR were the main factors predicting deterioration of kidney function during follow-up [35] . In another study, Bilen et al [36] evaluated 185 subjects with eGFR < 60 mL/min per 1.73 m² undergoing PCNL and found the average preoperative eGFR substantially improved from 42.4 to 48.4 at three months followup.…”
Section: Retrograde Intrarenal Surgerymentioning
confidence: 97%
“…The most common are hypotermia, bleeding, metabolic acidosis, serum electrolytes disturbances, urosepsis, and rarely death [39] . Anemia and underlying platelet dysfunction in patients with CKD may play important role in the high rate of transfusion [35,36] .…”
Section: Percutaneous Nephrolithotomymentioning
confidence: 99%
See 1 more Smart Citation
“…Dore et al [15] found that diabetes mellitus was the only systemic disease which had a significant effect on final SFR. Karami et al [16] reported that there is no significant difference (85 vs. 90%, p = 0.45) in the success rate between the patients older than 65 years and younger ones, and another study by Kurien et al [17] revealed that PCNL has an acceptable SFR (84%) in patients with chronic kidney disease. In the study of Resorlu et al [12], the final SFR decreased significantly with an increase in Charlson Comorbidity Index (90.8% in patients with no comorbidities, 95.4% in patients with score 1 and 83.9% in patients with score ≥2, p = 0.049).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Endoscopic procedure like PCNL needs continuous irrigation of fluids for better vision and to wash away stone fragments and blood clots formed. [3] Systemic absorption of irrigation fluids sometimes leads to fluid overload and electrolyte imbalances.…”
Section: Introductionmentioning
confidence: 99%